Hard Times, Hard Attitudes? The Effect of Economic Downturns on Gender Norms - Inés Berniell; Leonardo Gasparini; Mariana Marchionni; Mariana Viollaz (Institute of Labor Economics (IZA), 2024)
This paper examines the impact of economic fluctuations on social norms, specifically exploring the link between changes in unemployment and shifts in attitudes toward gender roles in the labor market. The results are not immediately obvious, as the literature suggests several potential mechanisms with conflicting outcomes. Using microdata from the World Values Survey for a panel of 103 countries that cover close to 90% of the world population, we estimate individual-level probability models of agreement with traditional gender roles over the period 1995 to 2021, including country and year fixed effects. We find that an increase in unemployment is associated to more conservative views about gender roles in the labor market. This result is remarkably robust across different groups and specifications. We also find that some contextual factors matter. In particular, the link between higher unemployment and more conservative views on gender roles is stronger in countries with, on average, higher gender inequality and lower female labor force participation. Overall, this study contributes to a growing body of research on the complex relationship between economic conditions, gender norms, and social change.
Keywords: J16; J21; J22; J31; 330; unemployment; business cycle; attitudes; social norms; gender values; gender